2019
DOI: 10.1186/s13068-019-1445-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptomic profiling of filamentous fungus during solid-state and submerged fermentation and identification of an essential regulatory gene PoxMBF1 that directly regulated cellulase and xylanase gene expression

Abstract: Background Solid-state fermentation (SSF) mimics the natural decay environment of soil fungi and can be employed to investigate the production of plant biomass-degrading enzymes. However, knowledge on the transcriptional regulation of fungal genes during SSF remains limited. Herein, transcriptional profiling was performed on the filamentous fungus Penicillium oxalicum strain HP7-1 cultivated in medium containing wheat bran plus rice straw (WR) under SSF (WR_SSF) and subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Overall, a 10-fold cost reduction for cellulase production in solid-state fermentation compared to submerged fermentation has been estimated (Tengerdy 1996). Recently, Zhao et al (2019) performed transcriptomic profiling of the filamentous fungus Penicillium oxalicum during solid-state and submerged fermentation and demonstrated, that the expression of major cellulase genes was higher under solid state conditions, while genes involved in the citric acid cycle were downregulated.…”
Section: Cellulase Production By Aerobic Fungal Biofilmsmentioning
confidence: 99%
“…Overall, a 10-fold cost reduction for cellulase production in solid-state fermentation compared to submerged fermentation has been estimated (Tengerdy 1996). Recently, Zhao et al (2019) performed transcriptomic profiling of the filamentous fungus Penicillium oxalicum during solid-state and submerged fermentation and demonstrated, that the expression of major cellulase genes was higher under solid state conditions, while genes involved in the citric acid cycle were downregulated.…”
Section: Cellulase Production By Aerobic Fungal Biofilmsmentioning
confidence: 99%
“…Recently, we compared transcriptional profiles of Penicillium oxalicum strain HP7-1 cultivated in liquid and solid media containing the same carbon source, and the results indicated that SSF elevated the expression of major cellulase genes and repressed the expression of genes involved in the citric acid cycle compared with levels in SmF cultures. Subsequently, a key regulator, P. oxalicum MBF1 (PoxMBF1), was identified, which negatively affected the production of cellulase and xylanase of P. oxalicum during SSF as well as SmF (9). However, this information is insufficient to elucidate the regulatory mechanism of cellulase and xylanase gene expression under SSF.…”
mentioning
confidence: 99%
“…Multiple efforts have been made to improve Ac resistance and elucidated mechanisms of stress resistance in yeast [4, 20, 21]. However, little attention is paid to the relationship between Ac resistance and atg22 , a small membrane-spanning protein on vacuole of S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%